Polygyny and sexual selection in red-winged blackbirds - Searcy, William A., 1950-; Yasukawa, Ken, 1949- (Monographs in behavior and ecology., 1995)
The purpose of this book is to explain why red-winged blackbirds are polygynous and to describe the effects of this mating system on other aspects of the biology of the species. Polygyny is a mating system in which individual males form long-term mating relationships with more than one female at a time. The authors show that females choose to mate polygynously because there is little cost to sharing male parental care in this species, and because females gain protection against nest predation by nesting near other females. Polygyny has the effect of intensifying sexual selection on males by increasing the variance in mating success among males. For females, polygyny means that they will often share a male's territory with other females during the breeding season and will thus be forced to adapt to frequent female-female interactions. This work reviews the results of many studies by other researchers, as well as presenting the authors' own results. Studies of red-winged blackbirds have ranged from long-term investigations of reproductive success and demography, to research on genetic parentage based on modern molecular methods, to a variety of experimental manipulations of ecological circumstances and behavior. Since the red-winged blackbird is one of the best studied species of any taxa in terms of its behavior and ecology, the authors have a particularly extensive body of results on which to base their conclusions. Originally published in 1995. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.